The Effect Of Endorser Credibility On Purchase Intention Mediated By Brand Attitude And Brand Credibility On Online Travel Agent Traveloka - Refi Rifaldi Windya Giri; Fairuuz Fikar Alfaruqi (Jurnal Manajemen Indonesia, 2023)
Online travel agencies (OTAs) in Indonesia, such as Traveloka, spend annually to endorse their brands through celebrities on TikTok to influence consumer perceptions of credibility and purchase intentions. This research explores the impact of celebrity endorsers’ expertise, trustworthiness, and attractiveness on brand attitude, brand credibility, and purchase intention within the context of online travel agencies (OTA). Recognizing the significance of celebrity endorsement for enhancing the purchasing behavior of consumers towards OTA brands, the findings of this study have important implications for how OTA companies can strategically adopt celebrity endorsement to sustain their customers' intention to purchase travel-related services. The study employs Partial Least Method-Structural Equation Modeling and includes 244 respondents, and data analysis was conducted using SEM analysis with WarpPLS 7.0 software. The results indicate a significant positive effect of celebrity endorser credibility on purchase intention through brand attitude and credibility. By using credible celebrities as endorsers, OTA companies, such as Traveloka in Indonesia, have been successful in influencing consumers' brand perception and building brand credibility, which in turn positively affects their purchase intention. The research findings highlight the importance of brand attitude as the most significant factor that impacts consumers' intention to purchase. Consequently, the study provides valuable insights for OTA companies, emphasizing the necessity of employing credible endorsers to build brand credibility and positively influence consumers' attitudes and purchase intention. Keywords— Brand attitude; Brand Credibility; Endorser Credibility; Purchase Intention; Online Travel Agencies